EDUKASI TENTANG PENGETAHUAN DAN BUDAYA MASYARAKAT DALAM PEMAMFAATAN JAMBAN DENGAN PRILAKU BABS DI DESA NAMO PAKAM KECAMATAN NAMO RAMBE - Tarigan, Usaha Satria Pratama (INSTITUT KESEHATAN DELI HUSADA, 2025)
Open defecation (OD) remains a widespread environmental health issue, including in Namo Pakam Village, Namo Rambe District. This study aims to explore the relationship between knowledge levels and community culture in latrine utilization and its impact on OD practices. This research employs a quantitative method with an analytical survey approach, using purposive sampling to select respondents. A total of 56 residents of Namo Pakam Village participated as research samples. Data collection was conducted through questionnaires, direct observation, and in-depth interviews. The findings indicate that low knowledge levels and cultural influences that perceive OD as an acceptable habit are the primary factors contributing to the low utilization of latrines. Additionally, limited sanitation facilities and a lack of awareness regarding the health risks of OD further exacerbate the situation. Statistical analysis reveals a significant relationship between knowledge, community culture, and OD practices. Therefore, interventions through health education and improved access to sanitation facilities are expected to drive behavioral changes toward healthier and more hygienic practices. In conclusion, social and educational-based approaches are key to addressing the issue of OD within the community.